HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN KEMAMPUAN SMASH PADA EKTRAKURIKULER BOLAVOLI DI SMP NEGERI 6 KOTA LUBUKLINGGAU - Handro Gustiawan; M. Rusni Eka Putra; Muhammad Suhdy (LP4MK STKIP PGRI Lubuklinggau, 2021)
The problem in this study is that volleyball extracurricular students at SMP Negeri 6 Lubuklinggau City still have jumps and punches in the weak category, this is due to the weak power of the students' leg muscles which causes the smash to be performed less than optimal. The research objective was to determine whether there was a relationship between the explosive power of the leg muscles and the smash ability of volleyball players at SMP Negeri 6 Lubuklinggau City. The variables of this study were the leg muscle explosive power as the independent variable, and the smash ability was the dependent variable. This type of research is correlational research. This research was conducted on 14 male volleyball extracurricular students at SMP Negeri 6 Lubuklinggau City. The instrument for collecting the explosive power of the leg muscles used the vertical jump test and the smash used the smash ability test. The data analysis technique used the product moment correlation formula. The results of the study showed that there was a relationship between the leg muscle explosive power (x) and the volleyball smash ability (y), the calculation result was rxy = 0.55 from this value can be categorized as moderate. The results stated that there was a significant relationship between the explosive power of leg muscles on the smash ability of volleyball extracurricular students at SMP Negeri 6 Lubuklinggau City, this was stated based on hypothesis testing where t hit = 2.280 > t tab = 2.178.